A Study on the Recruitment and Selection Process at Tata Consultancy Services, Nagpur - Khandale, Shrushti Neharu; Tekade, Atul B. (Journal of Neonatal Surgery, 2025)
Effective recruitment and selection processes are critical for ensuring organizational success and sustainability. This study examines the recruitment and selection strategies employed at Tata Consultancy Services (TCS), Nagpur, with an emphasis on their effectiveness in attracting, evaluating, and retaining top talent. Utilizing a mixed-methods approach, the research combines quantitative data analysis and qualitative insights to provide a comprehensive understanding of the strategies implemented by TCS. Key aspects such as job profiling, sourcing techniques, assessment methodologies, and decision-making frameworks are critically analysed. The study identifies best practices and potential areas of improvement within the existing system, highlighting the integration of technology and data analytics as transformative elements in optimizing recruitment efficiency. Furthermore, it explores the role of organizational culture and employer branding in influencing candidate perceptions and experiences throughout the hiring journey. The findings underscore the significance of aligning recruitment practices with organizational goals and employee aspirations, ultimately driving performance and reducing attrition rates. This research contributes to the broader discourse on human resource management by providing actionable insights for organizations aiming to enhance their talent acquisition strategies in an increasingly competitive job market